2019
DOI: 10.1021/jacs.9b09340
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up Creation of an Artificial Cell Covered with the Adhesive Bacterionanofiber Protein AtaA

Abstract: The bacterial cell surface structure has important roles for various cellular functions. However, research on reconstituting bacterial cell surface structures are limited. This study aimed to bottom-up create a cell-sized liposome covered with AtaA, the adhesive bacterionanofiber protein localized on the cell surface of Acinetobacter sp. Tol 5, without the use of the protein secretion and assembly machineries. Liposomes containing a benzylguanine derivative-modified phospholipid were decorated with a truncated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
0
11
0
1
Order By: Relevance
“…The surface-decorated liposomes were prepared by the conventional extrusion method followed by external insertion of BG-DSPE and reaction with SNAP-GFP, as shown in our previous study. 26 The Proteinase K treatment reduced the fluorescence intensity of the purified SNAP-GFP and the surface-decorated liposomes to 25% of the initial intensity (Figure 3A). In contrast, the fluorescence intensity of the liposomes encapsulating SNAP-GFP remained high after an 8 h incubation.…”
Section: Preparation Of Liposomes With Snap-gfp Localizedmentioning
confidence: 96%
See 2 more Smart Citations
“…The surface-decorated liposomes were prepared by the conventional extrusion method followed by external insertion of BG-DSPE and reaction with SNAP-GFP, as shown in our previous study. 26 The Proteinase K treatment reduced the fluorescence intensity of the purified SNAP-GFP and the surface-decorated liposomes to 25% of the initial intensity (Figure 3A). In contrast, the fluorescence intensity of the liposomes encapsulating SNAP-GFP remained high after an 8 h incubation.…”
Section: Preparation Of Liposomes With Snap-gfp Localizedmentioning
confidence: 96%
“…GUVs are appropriate for mimicking animal cells but not for mimicking bacterial cells, which are mimicked by large unilamellar vesicles (LUVs), i.e., liposomes 100–1000 nm in diameter, similar in size to viruses, exosomes, and bacteria. ,, The surface of LUVs, which are usually prepared using an extruder (the extruder method), can be decorated by proteins utilizing a chemical reaction with membrane-inserted lipid molecules linked with a functional group. Previously, we mimicked bacterial cells by preparing LUVs that capsulated enzyme molecules and were decorated with an adhesive bacterionanofiber protein. , However, it is difficult to localize proteins only inside the lipid bilayer of LUVs but not outside because liposomes produced by the extruder method involving dried lipid film preparation, buffer hydration, sonication and vortexing, freeze–thaw cycles, and extruder processing have a lipid bilayer that is identical in composition of the two leaflets . Although microfluidic devices have attracted attention in recent years to prepare liposomes with asymmetric membranes, they require sophisticated equipment, and it is challenging to adjust the flow rate conditions and chip design for creating liposomes with a diameter of 1 μm .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atomic force microscopy (AFM) revealed that the adhesion force of Tol 5 to a sharp silicon nitride probe was near 2 nN, which was 1-2 orders of magnitude stronger than that of other highly adhesive bacteria 17 . This characteristic nonspecific adhesiveness of Tol 5 cells is mediated by a single protein, AtaA 2,18,19 , a member of the trimeric autotransporter adhesin (TAA) family 3 . TAAs are outer membrane proteins of gram-negative bacteria and have been well studied as virulence factors because they enable binding to biotic molecules of mammalian host cells and, in some cases, to various abiotic surfaces 20,21 .…”
Section: Mainmentioning
confidence: 99%
“…Sistemas nanoestruturados biofuncionais podem ser sintetizados a partir da combinação de biomateriais sintéticos e biológicos, que por sua vez lhe conferem habilidade para mimetizar algumas funções, propriedades de superfície e características morfológicas inerentes às células vivas sem, no entanto, apresentar qualquer similaridade à estrutura biológica celular 2,9,10 . A funcionalização da superfície de sistemas celulares sintéticos com receptores, antígenos e grupos funcionais ligantes presentes em membranas celulares possibilita não só a comunicação intercelular, mas também capacidade de mimetizar (imitar) as principais funções celulares [11][12][13] . Além disso, similaridades estruturais e morfológicas aos tecidos biológicos vivos são determinantes à biomimetização das atividades celulares [14][15][16][17][18][19][20][21][22] uma vez que conferem características das células naturais em materiais não vivos, com amplo potencial de aplicações biomédicas muito promissoras [23][24][25] .…”
unclassified